2020
DOI: 10.1111/jvh.13414
|View full text |Cite
|
Sign up to set email alerts
|

The effect of universal infant vaccination on the prevalence of hepatitis B immunity in adult solid organ transplant candidates

Abstract: Background Hepatitis B virus (HBV) immunity is recommended to optimize outcomes after solid organ transplantation (SOT). This study assessed the prevalence and predictors of HBV immunity at the time patients were placed on transplant waiting list over a period from 1997 to 2019 in a low HBV endemic region. Methods Data were obtained from the University Hospitals Leuven transplant database. Minors and patients with past/current HBV infection were excluded. From 1986, Belgian patients are covered by the universa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Among vaccinated 18-to 21-year old blood donors in China, the prevalence of HBsAg accounted for 3.4% suggesting exposure to HBV not prevented by vaccination. 37 Both Koc et al 38 and Theeten et al 39 indicated that the vaccinated serostatus in Belgium was more prevalent in vaccinated birth cohorts targeted in infancy (more than 80%) than in those targeted in adolescence (about 40%-60%). Moreover, the self-reported coverage of vaccination against HBV between 1999 and 2017 in Flanders, Belgium, exceeded 90% of the infants from 2005 onwards while it was below 90% for adolescents up to 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Among vaccinated 18-to 21-year old blood donors in China, the prevalence of HBsAg accounted for 3.4% suggesting exposure to HBV not prevented by vaccination. 37 Both Koc et al 38 and Theeten et al 39 indicated that the vaccinated serostatus in Belgium was more prevalent in vaccinated birth cohorts targeted in infancy (more than 80%) than in those targeted in adolescence (about 40%-60%). Moreover, the self-reported coverage of vaccination against HBV between 1999 and 2017 in Flanders, Belgium, exceeded 90% of the infants from 2005 onwards while it was below 90% for adolescents up to 2017.…”
Section: Discussionmentioning
confidence: 99%